2010
DOI: 10.9755/ejfa.v22i4.4879
|View full text |Cite
|
Sign up to set email alerts
|

Character association in mulberry under different magnitude of salinity stress

Abstract: Information on interrelationships among traits is important for varietal development. Under stress conditions the magnitude of character association is known to change significantly. In mulberry such information on such aspects is lacking. Hence, the interrelationships of leaf yield and its component morphological, physiological and biochemical traits were investigated under four different salinity conditions using 11 genotypes. Correlation coefficient between leaf yield and its component traits was found chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Trait association analysis draws a clear image of inter-relationships and relative contribution of independent variables on dependent variables, which enables a plant breeder to make selection procedures for crop improvement (Dewey andLu, 1959 andBhat, 1973). Genetic variability and trait association studies for various agro-morphological traits in mulberry has been reported by various researchers in India (Sarkar et al, 1987;Bari et al, 1989;Susheelamma et al, 1998;Goel et al, 1998;Vijayan et al, 1998;Masilamani et al, 2000;Tikader and Roy, 2001;Tikader et al, 2004;Tikader and Dandin, 2005;Rahman et al, 2006;Doss et al, 2006;Banerjee et al, 2007;Mallikarjunnappa et al, 2008;Vijayan et al, 2010;Doss et al, 2011;Doss et al, 2012;Biradar et al, 2015 andSuresh et al, 2017). The North-Western Himalayan region of India is gifted with very rich diversity of mulberry with high morpho-genetic variability.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Trait association analysis draws a clear image of inter-relationships and relative contribution of independent variables on dependent variables, which enables a plant breeder to make selection procedures for crop improvement (Dewey andLu, 1959 andBhat, 1973). Genetic variability and trait association studies for various agro-morphological traits in mulberry has been reported by various researchers in India (Sarkar et al, 1987;Bari et al, 1989;Susheelamma et al, 1998;Goel et al, 1998;Vijayan et al, 1998;Masilamani et al, 2000;Tikader and Roy, 2001;Tikader et al, 2004;Tikader and Dandin, 2005;Rahman et al, 2006;Doss et al, 2006;Banerjee et al, 2007;Mallikarjunnappa et al, 2008;Vijayan et al, 2010;Doss et al, 2011;Doss et al, 2012;Biradar et al, 2015 andSuresh et al, 2017). The North-Western Himalayan region of India is gifted with very rich diversity of mulberry with high morpho-genetic variability.…”
Section: Introductionmentioning
confidence: 87%
“…It can be grown in diverse edapho-climatic conditions which require more productive hybrids for acclimatization in particular area (Tikader et al, 2004). It is the primary food plant of silkworm (Bombyx mori L.); hence, availability of good quality leaf has great impact on the sustainability and profitability of sericulture industry (Vijayan et al, 2010). Increased production of silk depends, to a great extent on increased leaf yield of mulberry plant (Sarkar et al, 1987).…”
Section: Introductionmentioning
confidence: 99%